2024
DOI: 10.1111/ffe.14217
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of three‐dimensional fatigue crack path selection in Mg alloy WE43 using high‐energy X‐ray diffraction microscopy

Duncan A. Greeley,
Jacob F. Adams,
Peter Kenesei
et al.

Abstract: Fatigue short‐cracks in Mg alloys display complex growth behavior due to high plastic anisotropy and crack path dependence on local microstructural features. In this study, the three‐dimensional crystallography of short‐crack paths in Mg alloy WE43 was characterized by mapping near‐field high‐energy X‐ray diffraction microscopy (HEDM) reconstructed grain maps to high‐resolution X‐ray CT reconstructions of the fracture surfaces in the crack initiation and short‐crack growth regions of six ultrasonic fatigue spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Although Mg-light RE alloys, including Mg-Nd and Mg-Sm alloys, are considered highly competitive aviation engineering materials, their high-temperature applications are still limited. The previous research indicated that the heavy RE elements, including Gd and Y, are effective in improving the high-temperature performance of Mg alloys [10][11][12][13][14]. The maximum solubility level of Gd is 23.5 wt.% in the α-Mg matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Although Mg-light RE alloys, including Mg-Nd and Mg-Sm alloys, are considered highly competitive aviation engineering materials, their high-temperature applications are still limited. The previous research indicated that the heavy RE elements, including Gd and Y, are effective in improving the high-temperature performance of Mg alloys [10][11][12][13][14]. The maximum solubility level of Gd is 23.5 wt.% in the α-Mg matrix.…”
Section: Introductionmentioning
confidence: 99%